Diversity of Metabolically Active Bacteria in Water-Flooded High-Temperature Heavy Oil Reservoir - Tamara N. Nazina; Natalya M. Shestakova; Ekaterina M. Semenova; Alena V. Korshunova; Nadezda K. Kostrukova; Tatiana P. Tourova; Liu Min; Qingxian Feng; Andrey B. Poltaraus (Frontiers in Microbiology, 2017)
The goal of this work was to study the overall genomic diversity of microorganisms of the Dagang high-temperature oilfield (PRC) and to characterize the metabolically active fraction of these populations. At this water-flooded oilfield, the microbial community of formation water from the near-bottom zone of an injection well where the most active microbial processes of oil degradation occur was investigated using molecular, cultural, radiotracer, and physicochemical techniques. The samples of microbial DNA and RNA from back-flushed water were used to obtain the clone libraries for the 16S rRNA gene and cDNA of 16S rRNA, respectively. The DNA-derived clone libraries were found to contain bacterial and archaeal 16S rRNA genes and the alkB genes encoding alkane monooxygenases similar to those encoded by alkB-geo1 and alkB-geo6 of geobacilli. The 16S rRNA genes of methanogens (Methanomethylovorans, Methanoculleus, Methanolinea, Methanothrix, and Methanocalculus) were predominant in the DNA-derived library of Archaea cloned sequences; among the bacterial sequences, the 16S rRNA genes of members of the genus Geobacillus were the most numerous. The RNA-derived library contained only bacterial cDNA of the 16S rRNA sequences belonging to metabolically active aerobic organotrophic bacteria (Tepidimonas, Pseudomonas, Acinetobacter), as well as of denitrifying (Azoarcus, Tepidiphilus, Calditerrivibrio), fermenting (Bellilinea), iron-reducing (Geobacter), and sulfate- and sulfur-reducing bacteria (Desulfomicrobium, Desulfuromonas). The presence of the microorganisms of the main functional groups revealed by molecular techniques was confirmed by the results of cultural, radioisotope, and geochemical research. Functioning of the mesophilic and thermophilic branches was shown for the microbial food chain of the near-bottom zone of the injection well, which included the microorganisms of the carbon, sulfur, iron, and nitrogen cycles.